PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN KERIPIK TEMPE - Murti, Niken Restu; Sundari, Ristina Siti; Heryadi, D Yadi (Universitas Galuh, 2023)
The Covid-19 pandemic has caused some food businesses to experience a decline in sales; where the pandemic occurred, and the enactment of the lockdown rules made a business suffer losses. However, it is different from the